Ground-truthing vegetation indices and models in northern Colorado rangelands - Behnke, Cassidy, author; Ocheltree, Troy, advisor; Tinkham, Wade, committee member; Stewart, Jane, committee member; Porensky, Lauren, committee member (Colorado State University. Libraries, 2025)
The sustainable management of rangeland ecosystems is becoming more challenging than ever with the increasing variation in climate patterns occurring across the globe. Rangelands are integral to the production of livestock and account for approximately 30% of land area in the United States. To the rangeland stakeholders who depend on these landscapes to produce forage for grazing livestock, longer periods of drought and intense summer heat are growing concerns. Adaptive rangeland management can help bring resilience to these working ecosystems but requires that pastures be constantly monitored in order to inform adjustments to management actions. Advancements in the application of novel technologies, such as remotely-captured imagery, can give rangeland managers this needed up-to-date insight into the health of vegetation in their pastures. A variety of spectral indices and biomass models, made from remotely-captured imagery, have been shown to correlate with forage conditions in grassland ecosystems with mixed success, but few have been tested in Northern Colorado's semi-arid grasslands under drought. Thus, the goal of my project is to investigate the application of vegetation indices in predicting forage conditions in a semi-arid ecosystem over the course of an irregularly dry growing season.